Clinical Implications of Incidental Inferior Vena Cava Filter Abnormalities on Computed Tomography. (30th April 2016) - Jeong, Daniel; Sweeney, Jennifer; Kis, Bela; Biebel, Benjamin; Choi, Junsung
Abstract : Inferior vena cava (IVC) filters were born from 19th-century attempts to mechanically interrupt blood flow in the IVC, with the goal to prevent the embolization of lower extremity venous thrombi to the pulmonary arteries. The first IVC filter was placed in 1967, and in 1973, Dr. Lazar Greenfield introduced the filter design upon which modern filters are based. Since its initial development, the clinical indications for IVC filter placement have remained controversial.